Kajian Feminisme Dalam "Novel Cantik Itu Luka" Karya Eka Kurniawan - Anisa Kurniawati; Lili Liana; Nandya Putriani Asharina; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This journal aims to this describe kinds of gender inequality, sexual violence, and the main character struggle named Dewi Ayu to fight against women's downtrodden over men in post-colonial era in a novel Cantik Itu Luka by Eka Kurniawan. The way text reveals the ideas of the characters is less-explicit and tend to have depraved behavior even you unexpected form and direction. the patriarchy damages the main character pleasant to become a prostitute and assume that a woman is just stereotype and inferior. This research is based on the feminism-analysis theory. The data analyzed shows that the figure Dewi Ayu is a form of negotiation toward the colonialism.